Navigating Employment: Exploring the influence of organizational culture and person-organization fit in recruitment decisions - Caoile, Honey Katherine Angela P.; Cutara, Reynalyn A.; Estiola, Theresa A.; Mapanao, Michaela Katrine D.; Saguddaquil, Ma Eloisa B.; Tagala, Izelle Joy D. 4 0 16; 5
u
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2